Wherever I go, I will always be a loyal American : schooling Seattle's Japanese Americans during World War II - Pak, Yoon K. (Studies in the history of education (RoutledgeFalmer (Firm)) ;, 2002)
This is the story of how the Seattle public schools responded to the news of its Japanese American (Nisei) students' internment upon the signing of Executive Order 9066 by President Franklin D. Roosevelt on February 14, 1942. Drawing upon previously untapped letters and compositions written by the students themselves during the time in which the bombing of Pearl Harbour and the internment order took place, Yoon Pak explores how the schools and their students attempted to cope with evident contradiction and dissonance in democracy and citizenship. Emerging from the school district's tradition of emphasizing equality of all races and the government's forced evacuation orders based on racial exclusion, this dissonance became a real and lived experience for Nisei school chidren, whose cognitive dissonance is best revealed in poignant phrases like "I am and will always be an American citizen."